1991
DOI: 10.1007/bf01716195
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian vein catheterization in critically ill children: Analysis of 322 cannulations

Abstract: Complications in 322 percutaneous subclavian vein catheters placed in 272 children by the infraclavicular approach were investigated prospectively. Ages ranged from 4 days to 15 years. Incidents during catheter introduction occurred in 13 cases, and were more common when insertion was on the right side (p less than 0.01). Nine (2.8%) required urgent treatment: (6 pneumothorax, 1 hydrothorax, and 2 hemothorax). Anomalous lodging of the catheter tip was more common when insertion was on the right side (p less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 36 publications
0
34
0
4
Order By: Relevance
“…Abstracts for which there was no agreement as to the inclusion were analyzed jointly and the decision was made by consensus. Thus, 84 (80 articles and four theses) were ob-tained for detailed reading by the same two authors independently 27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,…”
Section: Methodsmentioning
confidence: 99%
“…Abstracts for which there was no agreement as to the inclusion were analyzed jointly and the decision was made by consensus. Thus, 84 (80 articles and four theses) were ob-tained for detailed reading by the same two authors independently 27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,…”
Section: Methodsmentioning
confidence: 99%
“…We found that SVC has a few advantages. For example, SVC has a lower risk of infection than femoral venous catheterization [6]. It is also less difficult than internal jugular vein (IJV) catheterization to perform in infants with short necks and larger-than-usual head-to-body proportions [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…3,4,9,10,12,13,16 Performing the procedure with the patient sedated resulted in greater success rates than carrying out catheterization with the patient conscious. We believe that rendering the patient immobile facilitates the identification of anatomical points and prevents the needle from becoming displaced from the vein during introduction of the catheter, increasing the success rate.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10,18,19 Pneumothorax is a complication that can put patient's art risk of death, and its incidence in the literature varies from 0.2 to 2.4%. 1,9,10,18,19 In our study, this complication 12,20 It is possible that this parameter for defining experience should be reassessed, although it has not been adopted as a rule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation